Manufacture of nitric acid - Carating, Eleanor; Jongco, Lourdes; Sideco, Rosario (Diliman, Quezon City College of Engineering, 1962)
The market shows that the consumption of nitric acid is equal to its importation and it is not being produced here in the Philippines. The conclusions we have drawn from this reports are that first; Erection of this plant will not be feasible since the sales price we had computed shows that it is greater than that when it is imported. Secondly, that the equipment to be used are all imported and will cost so much since there is no manufacturer here in the Philippines. Thirdly, most of the equipment are made of stainless steel which is expensive. Fourth, the catalysts used are expensive too.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plnts; Nitric acid